2023
DOI: 10.3389/fnut.2023.1121717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of imbalance in dietary macronutrients on blood hemoglobin levels: a cross-sectional study in young underweight Japanese women

Abstract: BackgroundIron deficiency and underweight are common nutritional problems among young Japanese women, many of whom show unhealthy dietary patterns owing to a desire for thinness. We conducted a cross-sectional analysis of the relationship between iron status, nutritional status, and dietary intake among young Japanese women with underweight to identify dietary risk factors for iron deficiency.MethodsOf the 159 young women (18–29 years of age) enrolled, 77 underweight and 37 normal-weight women were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A low level of vitamin D is reportedly associated with age-related health issues, such as sarcopenia, frailty, cognitive functional decline, and dementia [54][55][56][57][58][59][60][61][62][63][64][65]. Iron-deficiency anemia is a serious health issue due to the desire for thinness among young women in Japan [66]. Underweight young women in Japan also exhibit a low intake of dietary fiber, calcium, iron, and vitamin D [67].…”
Section: Selection Of Nutrients To Encouragementioning
confidence: 99%
“…A low level of vitamin D is reportedly associated with age-related health issues, such as sarcopenia, frailty, cognitive functional decline, and dementia [54][55][56][57][58][59][60][61][62][63][64][65]. Iron-deficiency anemia is a serious health issue due to the desire for thinness among young women in Japan [66]. Underweight young women in Japan also exhibit a low intake of dietary fiber, calcium, iron, and vitamin D [67].…”
Section: Selection Of Nutrients To Encouragementioning
confidence: 99%
“…38 Additionally, it has been observed that substituting dietary fat with protein, while maintaining isocaloric conditions, leads to increased hemoglobin levels. 39 Although research exploring the association between dietary protein and AAC remains limited, it is noteworthy that dietary protein intake holds significance as a crucial component within the Healthy Eating Index 2015 (HEI-2015) 40 and the Prospective Urban Rural Epidemiology (PURE) healthy diet score. 41 Dietary fiber has been extensively shown to possess protective properties against CVD.…”
Section: Food and Function Papermentioning
confidence: 99%